Dectin-1 participates in the immune-inflammatory response to mouse Aspergillus fumigatus keratitis by modulating macrophage polarization - Guibo, Liu; Chunxu, Dong; Biao, Chen; Zhaolei, Hu; Wenwen, Liu; Xiangnan, Ji; Wentao, Peng; Hongmin, Chang; Yonghua, Li; Guoqiang, Zhu (Frontiers in Immunology, 2024)
Fungal keratitis (FK) is a severe corneal disease that may cause vision loss. Previous studies indicate that the innate immune response produces the most eﬀective anti-Aspergillus immune resistance. Dectin-1, a pattern-recognition receptor (PRR) family plays an important role in the innate immune response of fungal keratitis. In this study, we aimed to further explore the role of Dectin-1 in the A. fumigatus infected cornea. Our study revealed that Dectin-1 regulates macrophage recruitment and polarization and plays a key role in corneal antifungal innate immunity. Our study also revealed that Dectin-1 may regulate changes in macrophage phenotype-associated factors through the MAPK cell signaling pathway.